Collective enhancements in the level densities of Dy and Mo isotopes - Rahmatinejad A. Azam; Shneydman T. M. Timur Markovich; Antonenko N. V. Nikolay Viktorovich; Bezbakh A. N. Anna Nikolaevna; Adamyan G. G. Gurgen Grigorjevich; Malov L. A. Leonard Aleksandrovich (2020, 2020)
Title screen